The Integration Of Cultural Resources Management In Disaster Management At Special Region Province Of Yogyakarta (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2017)
The Republic of Indonesia Law number 24 year 2007 on disaster emphasizes that the protection of national assets is in line with Law No. 11 year 2010 on the cultural heritage. Yogyakarta Province has 12 disaster hazards and has five complete archaeological cultural layers in Indonesia. In the event of a disaster, potential damage to the cultural heritage is exposed. The archaeological cultural layer consists of prehistoric, classical, Islamic and colonial. The lack of research related to cultural heritage in the province resulting in increasing vulnerability of cultural heritage and society. Using qualitative method with in-depth interview, the aim of this study is to analyse the management of cultural heritage from the perspective of disaster management. Archaeological cultural layers that embedded into the realm of cultural heritage is defined as a national asset that should be protected. The result shows that the management of cultural resources in the province is not yet integrated with disaster management. However, the results of the archaeological identification of cultural heritage in each cultural layer in Yogyakarta showed the development of community adaptation to the disaster. Utilization of cultural heritage as an element of the panca gatra has been impartial that affected the regional resilience and security in facing the disaster. Both of these problems can be overcome by integrating the cultural resources management and disaster management, the establishment of an emergency response team on cultural preservation, and disaster risk analysis on cultural heritage that annexed by BPBD and Cultural Office of Yogyakarta Province.